Pass-through of International food prices to domestic ination during and after the great recession: evidence from a set of Latin American economies (2011)
We examined how international food price shocks have impacted local ination processes in Brazil, Chile, Colombia, Mexico, and Peru in the past decade -- Using impulse-response analysis coming from cointegrated VARs, we wind that international food ination shocks take from one to six quarters to pass through to domestic head-line ination, depending on the country -- In addition, by calculating the elasticity of local prices to an international food price shock, we found that this pass-through is not complete -- We also take a closer look at how this type of shock affects local food and core prices separately, and asses the possibility second round effects over core ination stemming from the shock -- We wind that a transmission to headline prices does occur, and that part of the transmission is associated with rising core prices both directly and through possible second round effects, which implies a role for monetary policy when such a shock takes place -- This is especially relevant given that international food prices have recently been on an upward trend after falling considerably during the Great Recession